Pengaruh Konsolidasi Lahan Perkotaan Terhadap Harga Tanah di Ringintelu, Kelurahan Kalipancur - Kota Semarang - Mulyanti, Wuri (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
Changes in Semarang city is marked by the process of urbanism as an increased need caused widespread land settlements, economic facilities, trade and services as well as network infrastructure. This causes physical changes in the environment and the seizure of the land so that the price of land had become unmanageable. One of the government's efforts to unravel this problem is the structuring of the environment through urban land consolidation program. The program is expected to increase the price of the land, so it will not show the existence of idle land / "idle land" as in other research sites. It is what lies behind the importance of research on the effects of urban land consolidation in Ringintelu, Kalipancur Village - Semarang. The goal is to assess the effect of urban land consolidation on the price of land in Ringintelu, Kalipancur Village - Semarang. Methods this study uses a quantitative approach to factor analysis, multiple regression crosstab and to determine the level of the relationship and influence. The results obtained in this study is the relationship between land consolidation with the price of land in Ringintelu, Kalipancur Village - Semarang. This relationship affects 81.1 to rising land prices by 400% to 900% which are not directly affected by the consolidation program. The influence is said to be directly due to factors such as accessibility and infrastructure development occurs as a result of land consolidation program as well as the influence of other factors.